Parents’ Perception of Chemistry Teachers’ Instructional Efficiency in Secondary Schools in Idah Local Government Area, Kogi State - Achimugu, Lawrence (American Journal of Education and Learning, 2019)
The study investigated the parents’ perception of chemistry teachers’ level of instructional efficiency in secondary schools in Idah Local Government Area of Kogi State. Two research questions guided the study. A descriptive survey design was used.The entire population of 718 parents from 8 public senior secondary schools were samples. The instrument used for data collection was a 22-items structured questionnaire developed by the researcher. The instrument was validated and the reliability was established using Combach alpha (r=0.77).Mean and standard deviation were used to answer research questions. The results revealed the chemistry teachers were inefficient in their following tasks: punctuality to the class, encouraging students to participate in science club, inviting parents/community resource persons as guest instructors among others. Also the study revealed the factors that inhibit chemistry teachers’efficiency in their instructional roles to include: lack of fund, inadequate instructional materials, poor payment/delay in payment of teachers’ salaries, shortage and inadequate training of teachers. Recommendations were made to include that parents should be encouraged to assess chemistry teachers regularly and the feedback should be used to improve chemistry teacher instructional roles among others.